1978
DOI: 10.1093/ajcn/31.12.2167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a high protein (meat) intake on calcium metabolism in man

Abstract: The effect of a high protein (meat) intake of 2 g/kg on the calcium excretions and retention and on the intestinal calcium absorption was studied in man. In the control study the protein intake averaged 1 g/kg. The studies were carried out during a low calcium intake of 200 mg/day and a normal calcium intake of 800 mg/day. Two additional studies were carried out during a calcium intake of 1100 mg/day and one during a 2000 mg calcium intake. During the high protein-low calcium intake and during the 800 mg calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(25 citation statements)
references
References 43 publications
5
20
0
Order By: Relevance
“…In this study, male elderly volunteers had urinary calcium loss at levels similar to those described in the literature [13,14], which did not change during the period of calcium supplement or during the period of high-protein intake. Although the diet may have varied in some of its items, huge differences certainly did not occur and, as all subjects received biological protein with similar amounts of sulfur amino acids, diet variations had little or no influence on the results.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, male elderly volunteers had urinary calcium loss at levels similar to those described in the literature [13,14], which did not change during the period of calcium supplement or during the period of high-protein intake. Although the diet may have varied in some of its items, huge differences certainly did not occur and, as all subjects received biological protein with similar amounts of sulfur amino acids, diet variations had little or no influence on the results.…”
Section: Discussionsupporting
confidence: 76%
“…These high-protein diets have been shown to increase glomerular filtration rate and to reduce tubular calcium reabsorption, with the occurrence of hypercalciuria [11,12]. However, these findings could not be reproduced with a high-protein meat diet [13][14][15][16]. Also, most studies have been carried out in young subjects and the applicability of their results to the elderly population, on a mixed vegetable:animal high-protein diet remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the groups receiving higher protein diets generally also consume higher amounts of dietary phosphorus. Dietary phosphorus has been found to mitigate protein-induced hypercalciuria (46,47,52,53). It is suggested that the high phosphorus content of most foodstuffs containing dietary protein may inhibit protein-induced hypercalciuria and bone loss (12,52).…”
Section: Discussionmentioning
confidence: 99%
“…Increased urinary calcium excretion was also observed in omnivorous than in vegetarian women (Ball and Maughan, 1997) or in subjects following an Atkins diet (Reddy et al, 2002). However, other studies reported no change in the level of urinary calcium with the consumption of high-meat diets compared with low-meat diets (Spencer et al, 1978(Spencer et al, , 1983(Spencer et al, , 1988. The hypercalciuric effect of HP diets certainly depends on the nature of the dietary protein, and food with HP contents, such as meat or dairy products, also contain components that limit urinary calcium excretion.…”
Section: Protein Intake Urinary Calcium and Acid Excretions And Calcmentioning
confidence: 95%